Dr. Mitja Deisinger (1942–2026) - Zobec, Jan (Pravnik, 2026)
Dr. Mitja Deisinger (1942–2026) was one of the most prominent Slovenian scholars of criminal and constitutional law and a long-serving President of the Supreme Court of the Republic of Slovenia. Since 2008, he also served as a member of the editorial board of the journal Pravnik. Through his extensive scholarly work - especially his commentaries on criminal law legislation - he left a significant mark on Slovenian legal scholarship. He devoted particular attention to issues of corporate criminal liability, corruption, money laundering, and the protection of economic interests. His work extended beyond criminal law to constitutional law and broader social issues. As a judge of the Constitutional Court, he enriched constitutional jurisprudence with his well-reasoned separate opinions. Between 1997 and 2003, he served as Presi- dent of the Supreme Court, contributing to its modernisation and strength- ening judicial independence. He advocated for European values and was a co-founder of the Conference of Presidents of European Supreme Courts. He advocated redress for injustices committed under the totalitarian regime and supported alignment with European standards. He was distinguished by his human warmth, optimism, respect for others, and strong moral integrity. He leaves a lasting professional and personal legacy in the Slovenian legal community and society at large.
Keywords: constitutional law; corporate criminal liability; criminal law; Deisinger, Mitja; judicial independence; kazensko pravo; odgovornost pravnih oseb; sodniška neodvisnost; Supreme Court; ustavno pravo; Vrhovno sodišče